A RESECTED CASE OF SYNCHRONOUS DOUBLE CANCER OF THE ESOPHAGUS AND RECTUM - MORI, Masaharu; TAKEUCHI, Tsutomu; MINAGHI, Shinichi; SHIRAI, Hiroyuki; NAKA, Takuji; KIMURA, Akihiko (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 1999)
A 48-year-old man was admitted to the hospital because of fresh anal bleeding and pyrosis. Preoperative examination revealed advanced esophageal cancer (Im, 3'type) and rectal cancer (Rb, 2'type). Under a diagnosis of synchronous double primary cancer of the esophagus and rectum, an operation was performed on one-step approach. A subtotal esophagectomy with lymph node dissection and reconstruction of esophagus by gastric roll was performed, followed by a low anterior resection for the rectal cancer. Postoperative course was uneventful, but pharyngeal, tongue and mediastinal lymph nodes metastases of the esophageal cancer occurred. Radiation and chemotherapy were added, but the patient died 2 years after the operation. Pre-operative laboratory data showed a slight immunodeficient tendency and postoperative immunohistochemical examination revealed genetic arrangement of p 53 cancer suppressed gene in both the esophageal and rectal cancers. It was suggested that carcinogenesis might correlate with immunodeficiency and genetic alteration in synchronous multiple cancer.